Supersensitive Odorant Receptor Underscores Pleiotropic Roles of Indoles in Mosquito Ecology - Ruel, David M.; Yakir, Esther; Bohbot, Jonathan D. (Frontiers in Cellular Neuroscience, 2019)
Mosquitoes exhibit highly diverse and fast evolving odorant receptors. The indole-sensitive odorant receptor gene clade, comprised of Or2 and Or10 is a notable exception on account of its conservation in both mosquito subfamilies. This group of paralogous genes exhibits a complex developmental expression pattern in Aedes aegypti: AaegOr2 is expressed in both adults and larvae, AaegOr10 is adult-specific and a third member named AaegOr9 is larva-specific. OR2 and OR10 have been deorphanized and are selectively activated by indole and skatole, respectively. Using the two-electrode voltage clamp of Xenopus oocytes expressing Ae. aegypti ORs, we show that AaegOR9 is supersensitive and narrowly tuned to skatole. Our findings suggest that Ae. aegypti has evolved two distinct molecular strategies to detect skatole in aquatic and terrestrial environments, highlighting the central ecological roles of indolic compounds in the evolutionary and life histories of these insects.